(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Mutual funds serve as popular investment vehicles, attracting a diverse range of investors aiming for diversified, professionally managed portfolios. This study investigates the evolving information needs of mutual fund investors in the dynamic financial landscape. The study combines a comprehensive literature review with empirical data analysis to identify key areas of information importance and the extent of awareness of the mutual fund investors. The study employs a combination of primary and secondary data, with a stronger emphasis on the significance of primary data. The primary data was gathered through structured questionnaires distributed among individual investors residing in Silchar City. The respondents were identified using a snowball sampling technique. Primarily, descriptive statistics and rankings were employed to analyze the gathered data. The outcomes of the statistical analysis reveal that around 50% of the respondents displayed a moderate to high level of awareness regarding the occurrences within the mutual fund industry. Consequently, the study aimed to identify the sources of information or specific details that investors are pursuing, contributing to their heightened awareness. The investigation revealed that the key pieces of information they sought included benchmark indices, ratings from rating agencies, potential tax benefits offered by the fund, and Net Asset Value (NAV), among others. Observations have indicated that demographic factors play a crucial role. There is potential for further research to delve into these factors in greater detail.